2021
DOI: 10.3389/fgene.2021.760182
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Biomarkers to Predict the Prognosis of Biliary Atresia by Weighted Gene Co-Expression Network Analysis

Abstract: The prognosis of children with biliary atresia (BA) after Kasai operation remains difficult to predict, and liver fibrosis is closely related to the prognosis of children with BA. We aimed to find biomarkers for native liver survival (NLS) prediction by weighted gene co-expression network analysis (WGCNA). The biological processes and signal pathways that biomarkers involved in were further analyzed by bioinformatics. Quantitative Real-time PCR, Western blot and immunohistochemistry was performed to detect bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…We believe that it may be related to the mechanism of BA fibrosis. Moreover, it was proposed to be related to liver fibrosis in BA and involved in BA development (5). Thus, we initially evaluated the expression of LECT2 in liver tissue and serum of patients with BA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe that it may be related to the mechanism of BA fibrosis. Moreover, it was proposed to be related to liver fibrosis in BA and involved in BA development (5). Thus, we initially evaluated the expression of LECT2 in liver tissue and serum of patients with BA.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it may be related to the mechanism of BA fibrosis. Moreover, it was proposed to be related to liver fibrosis in BA and involved in BA development ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kong et al . 101 found increased expression of leukocyte cell-derived chemotaxin 2 (LECT2) mRNA in the liver tissues of children with BA. Another study found that LECT2 was also highly expressed in the sera of children with BA.…”
Section: Other Potential Biomarkersmentioning
confidence: 96%